Influence of apocynin on cardiac remodeling in rats with streptozotocin-induced diabetes mellitus - Gimenes, R. [UNESP]; Gimenes, C.; Rosa, C. M. [UNESP]; Xavier, N. P. [UNESP]; Campos, D. H.S. [UNESP]; Fernandes, A. A.H. [UNESP]; Cezar, M. D.M. [UNESP]; Guirado, G. N. [UNESP]; Pagan, L. U. [UNESP]; Chaer, I. D. [UNESP]; Fernandes, D. C.; Laurindo, F. R.; et al. (Springer Nature, 2018)
Background: Increased reactive oxygen species (ROS) generation in diabetes mellitus (DM) is an important mechanism leading to diabetic cardiomyopathy. Apocynin, a drug isolated from the herb Picrorhiza kurroa, is considered an antioxidant agent by inhibiting NADPH oxidase activity and improving ROS scavenging. This study analyzed the influence of apocynin on cardiac remodeling in diabetic rats. Methods: Six-month-old male Wistar rats were assigned into 4 groups: control (CTL, n=15), control+apocynin (CTL+APO, n=20), diabetes (DM, n=20), and diabetes+apocynin (DM+APO, n=20). DM was induced by streptozotocin. Seven days later, apocynin (16mg/kg/day) or vehicle was initiated and maintained for 8weeks. Left ventricular (LV) histological sections were used to analyze interstitial collagen fraction. NADPH oxidase activity was evaluated in LV samples. Comparisons between groups were performed by ANOVA for a 2×2 factorial design followed by the Bonferroni post hoc test. Results: Body weight (BW) was lower and glycemia higher in diabetic animals. Echocardiogram showed increased left atrial diameter, LV diastolic diameter, and LV mass indexed by BW in both diabetic groups; apocynin did not affect these indices. LV systolic function was impaired in DM groups and unchanged by apocynin. Isovolumic relaxation time was increased in DM groups; transmitral E/A ratio was higher in DM+APO compared to DM. Myocardial functional evaluation through papillary muscle preparations showed impaired contractile and relaxation function in both DM groups at baseline conditions. After positive inotropic stimulation, developed tension (DT) was lower in DM than CTL. In DM+APO, DT had values between those in DM and CTL+APO and did not significantly differ from either group. Myocardial interstitial collagen fraction was higher in DM than CTL and did not differ between DM+APO and CTL+APO. Serum activity of antioxidant enzymes glutathione peroxidase, superoxide dismutase (SOD), and catalase was lower in DM than CTL; apocynin restored catalase and SOD levels in DM+APO. Myocardial NADPH oxidase activity did not differ between groups. Conclusion: Apocynin restores serum antioxidant enzyme activity despite unchanged myocardial NADPH oxidase activity in diabetic rats.
Keywords: Diabetic cardiomyopathy; Echocardiogram; Heart failure; Myocardial function; NADPH oxidase; NADPH oxidase blocker; Oxidative stress; Papillary muscle; Rat; Ventricular function